Intraductal carcinoma of the prostate (IDC‐P) lowers apparent diffusion coefficient (ADC) values among intermediate risk prostate cancers. Issue 1 (25th December 2018) - Currin, Stephen; Flood, Trevor A.; Krishna, Satheesh; Ansari, Afshin; McInnes, Matthew D.F.; Schieda, Nicola
Abstract : Background: Prostatic intraductal carcinoma (IDC‐P) is an aggressive variant of prostate cancer (PCa) characterized by proliferation of malignant cells within prostatic ducts/acini and nucleomegaly. Purpose/Hypothesis: To compare apparent diffusion coefficient (ADC) values and Prostate Imaging and Data Reporting System (PI‐RADS) v. 2 scores in intermediate risk (International Society of Urological Pathology [ISUP] Grade Group [GG] 2 and 3) PCa with/without IDC‐P to determine if IDC‐P alters the MRI appearance of PCa. Study Type: Retrospective, case–control. Population: Fifteen consecutive men with ISUP GG 2/3 (Gleason score 3+4 = 7 [ N = 4], 4+3 = 7 [ N = 11]) PCa with IDC‐P diagnosed at radical prostatectomy were compared with: 1) ISUP GG 2/3 PCa without IDC‐P (matched for percentage Gleason pattern 4), and 2) ISUP GG 4 and 5 (Gleason score 8/9) PCa without IDC‐P. Field Strength/Sequence: 3T multiparametric MRI. Assessment: Two blinded radiologists (R1/R2) measured mean ADC, ADC.ratio (ADC.tumor/ADC.normal peripheral zone) and assigned PI‐RADS v2 scores. Statistical Tests: Chi‐square and analysis of variance (ANOVA). Results: There were no differences in age, prostate serum antigen, tumor size, or stage between groups ( P = 0.063‐0.912). Tumors with IDC‐P had lower mean ADC and ADC.ratio (0.741 ± 0.152 mm 2 /sec and 0.44 ± 0.07) compared with ISUP GG 2/3 tumors without IDC‐P (0.888 ± 0.167 mm 2 /sec and 0.62 ± 0.14), P = 0.012 and <0.001; and did not differ compared with ISUP GG 4/5 tumors (0.705 ± 0.141 mm 2 /sec and 0.44 ± 0.08), P = 0.509 and 0.868. Tumors with IDC‐P were nearly all PI‐RADS v2 score 5 (14/15) compared with ISUP GG 2/3 tumors without IDC‐P (10/15 R1, 8/15 R2) and GG 4/5 tumors (9/15), ( P = 0.040 = 0.092). Agreement in PI‐RADS v2 scoring was moderate (K = 0.68). Data Conclusion: ISUP GG 2 and 3 (intermediate risk, Gleason score 7) PCa with IDC‐P have lower ADC compared with tumors without IDC‐P with a similar percentage of Gleason pattern 4 and resemble ISUP GG 4 and 5 high risk tumors on MRI. IDC‐P lowers ADC values among intermediate risk prostate cancers. Level of Evidence : 3 Technical Efficacy Stage : 2 J. Magn. Reson. Imaging 2019;50:279–287.